(untitled) (Journal of Geography and Environmental Management, 2019)
Held characteristic of geoecological state of geosystems on the sites of background key and located in the zone of strong anthropogenic contamination. Found a significant increase in the concentration of SO42-, Cl-, NO2-, NO3 – and Pb2+in water, on the approach to the emission source. Quantitative variation-statistics content of macro-and microelements, which reflect the intensity, character and features of their accumulation in the waters. Map of geosystems Sarysu basin.